Peranan Syekh Silau Laut dan Kontribusinya Terhadap Perkembangan Islam di Kecamatan Silau Laut Kabupaten Asahan - Amin, Amirul (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
Tuan Syekh Abdurrahman Silau is an important scholar who brought the progress of Islam in Asahan, which started from Silau Lama Village. It started when he was determined to meet Sultan Asahan named Tengku mAsbun, the younger brother of Tengku Aidil, to ask for forest land that was not yet inhabited by people. So Sultan Asahan gave him the Glare of the Sea forest lan in 1319 Hijriah/1909 AD. Then he and his family and relatives opened up the Glare of the sea forest land. This research is a qualitative research type of field research (field study) using historical methods. The data collection techniques in this study used participatory observation techniques with complete participation, semi-structured interview techniques, and used literature studies in the form of photos of library studies, journals and online articles about Mr. Sheik Glare of the sea. The results of this research are that Mr. Syekh Abdurrahman Silau Laut is the founder of the village of Glare of the sea, of course he has given of done a lot for the construction of the Glare of the sea. Starting from begging for land, clearing forests where there are still many wild animals to building infrastructure, to what was once a forest to become a small village to now a sub-district.